Contrasting responses of native and introduced mammal communities to fire mosaics in a modified landscape. Issue 6 (16th June 2022) - Zylinski, Simeon; Swan, Matthew; Sitters, Holly
Abstract: Planned fire is increasingly recognized as an important tool in conservation, but other factors such as land‐use change may hinder the ability of land managers to use fire for the benefit of biodiversity. The mosaic of past fires in native vegetation may interact with the mosaic of other land‐cover types in human‐modified landscapes, yet the effects of these interactions on mammal communities are unknown. We investigated the responses of ground‐dwelling mammal community composition and species richness to interactions between land cover and post‐fire vegetation growth‐stage mosaics in southern Australia. This fire‐prone, human‐modified landscape features a fine‐scale fire mosaic in native vegetation patches surrounded by pasture, horticulture, and peri‐urban environments. We measured the composition of land‐cover types and fire mosaics (landscape structure) at multiple scales of up to 1257 ha surrounding 129 study sites, and considered native and introduced species together and separately. Land‐cover composition was the primary driver of community composition: native species favored areas with a greater proportion of native heathy woodland, whereas introduced species were associated with landscapes comprising more cleared land. The fire mosaic also influenced community composition and species richness: greater growth‐stage diversity was associated with native habitat‐specialist communities and fewer introduced species. In areas with more cleared land, native species richness increased when there was a greater proportion of mid‐successional vegetation, demonstrating that the effect of fire mosaics on mammal diversity depended on land‐cover composition. The positive relationship between introduced species richness and cleared land extent was also stronger in recently burned sites than in other growth stages, suggesting that introduced species are well suited to more modified areas of the landscape. Land managers need to consider the underlying land‐cover composition and the potential interactions it may have with fire mosaics and species composition. In this landscape a greater diversity of growth stages may disadvantage introduced species yet an increase in mid‐successional vegetation in more modified areas would be likely to benefit native mammal communities. Our study highlights that fire management may need to be tailored depending on the context of land use and the species of interest.